Shaping Future Leaders: How Technology is Transforming Islamic Education in The Digital Age - Mursidin, Muthmainnah (AT-TURATS, 2023)
Islamic education has a rich tradition of instilling moral values, religious principles, and leadership qualities in young learners, laying the foundation for them to become ethical and responsible future leaders in Muslim societies. However, the advent of the digital age has brought about profound changes in education worldwide, introducing technology as a powerful tool that both enriches and challenges traditional educational approaches. This research aims to explore the intricate relationship between technology and Islamic education, with a particular focus on how technology is shaping the character development of future leaders in this digital era. This research employs a mixed-methods approach to comprehensively examine the multifaceted impact of technology on Islamic education. Participants include 20 students. The study involves structured questionnaires to collect quantitative data on students' experiences with technology-enhanced Islamic education, in-depth interviews with educators, students, and parents to gather qualitative insights, and content analysis of educational materials and digital resources used in technology-based Islamic education to assess their alignment with Islamic values and character development. In conclusion, technology has the potential to significantly impact character development and student engagement in Islamic education. However, its benefits must be harnessed thoughtfully, considering content quality and the necessity of responsible technology usage guidance. As we navigate the evolving landscape of Islamic education in the digital age, it is crucial to strike a delicate balance that leverages technology's benefits while ensuring the preservation of Islamic values. This research provides valuable insights for educators, parents, and institutions as they guide the next generation of leaders toward a harmonious fusion of faith and technology.